7. Pathophysiological basis of motor neuronal hyperexcitability in amyotrophic lateral sclerosis. Issue 3 (March 2016) - Shibuya, Kazumoto; Park, Susanna B.; Geevasinga, Nimeshan; Huynh, William; Simon, Neil G.; Menon, Parvathi; Howells, James; Garg, Nidhi; Noto, Yu-ichi; Iwai, Yuta; Nicholson, Garth A.; Vucic, Steve; et al.
Abstract : Objective: Motor neuronal hyperexcitability potentially contributes to motor neuron death in amyotrophic lateral sclerosis (ALS). We aimed to reveal pathomechanisms of motor neuron hyperexcitability in ALS. Methods: Threshold tracking transcranial magnetic stimulation and multiple excitability measurements were performed in 130 healthy controls (HC), 83 sporadic ALS (sALS) patients, 11 patients with superoxide dismutase-1 ( SOD-1 ) mutations, 16 C9orf72 hexanucleotide repeat expansions and 2 FUS mutations. Results: Compared to HC, in peripheral nerve excitability sALS had greater strength-duration time constant ( p   <  0.05), depolarizing threshold electrotonus ( p   <  0.0001) and superexcitability ( p   <  0.05) and smaller late subexcitability ( p   <  0.05). In cortical excitability, sALS had reduced short interval intracortical inhibition ( p   <  0.0001). These indices were not significantly different in SOD-1 and C9orf72, compared to sALS. Conclusion: These findings suggest both sALS and familial ALS have increased sodium currents, decreased potassium currents, rendering to peripheral nerve hyperexcitability. In addition, all ALS patients demonstrated decreased intracortical inhibition. Significance: Motor neuronal hyperexcitability may be a common feature in both sALS and familial ALS associated with different pathological bases.